Research on Negotiation Skills and Win-Win Strategies in Digital Trade Platforms - Zhang, Tianhao (Transactions on Economics, Business and Management Research, 2024)
The explosion of digital trade platforms is reshaping global business, yet practical negotiation skills remain a core challenge. This research highlights the necessity of developing negotiation skills and win-win strategies within digital trade environments. The case of Alibaba.com exemplifies the current state of digital trade and underscores the significant challenges faced by negotiators, including cultural differences, language barriers, complex logistics and supply chains, as well as issues of trust and verification. Enhanced tools for data analytics, communication, and third-party verification services are essential for achieving higher returns from negotiations, as demonstrated by Alibaba.com. However, persistent issues such as cultural misunderstandings and logistical complications require innovative solutions. The research suggests implementing advanced AI translation tools, cultural training modules, logistical solutions, and blockchain technology to improve transparency and trust within the system. These strategies are fundamental for enhancing negotiation efficiency, creating sustainable business relationships, and stimulating global commerce growth. Ultimately, this approach will provide digital trade platforms with a competitive edge, enhance customer satisfaction, and foster a more interconnected world in commerce.